Results on growing the seedlings of laminaria Saccharina japonica in the Center of Mariculture on Popov Island (Peter the Great Bay, Japan Sea) - T. N. Krupnova; O. A. Ponyrko (Известия ТИНРО, 2024)
Results on experimental cultivation of seedlings of laminaria kelp Saccharina japonica are considered. Growing of this species was conducted in the first time in the Center of Mariculture located on Popov Island in the coastal Japan Sea. Data on equipment of the modules for cultivation of early stages of algae and on environmental conditions for their optimal growth are presented. Diatoms influence on the growth of kelp seedlings is shown. The optimal dates for seeding the spores on artificial substrate frames and for the frames transplantation into the sea are determined that provides the most rational growing cycle in a forced mode.